Nigerian Federalism and the Unending Clamour for Restructuring: Which Way Forward? - Ahmed, Usman; Yusuf, Ramatu (Kashere Journal of Politics and International Relations, 2023)
A federal system entails coming together either wittingly or unwittingly of various nations of distinct socio-cultural and historical backgrounds, exploiting common geographical proximity to form a strong national government. The Nigerian experience however, appears that, the regional geographical entities that made up the Nigerian state were deliberately fused together by the British Colonial Authority for a vested interest. Although one thing that appears interesting in a federal system, is the constitutional division of powers between the central government on one hand and the governments of the federating units on the other. In the Nigerian model, the provision of the constitution has made the central government stronger being the only tier with powers to enforce the exclusive or national matters and correspondingly, makes the federating units weak and subordinates rather than coordinates. This arrangement perhaps made some people to see Nigerian federal structure as skewed and a quasi-form of federalism. This by and large ignited a clamour for restructuring as an option for a redress. The paper examines this phenomenon utilizing elite theory, with data largely obtained from secondary sources. The study adopts qualitative method of analysis with a finding revealing that poor leadership rather than the federal structure arrangement is mainly responsible for groups’ agitations on restructuring Nigerian state. Consequently, the paper recommends that good governance rather than restructuring provides immediate solution to the problems associated with Nigerian federalism.